Genotype distribution in Hepatitis C patients admitted to Erzincan Mengücek Gazi Training and Research Hospital - Yilmaz, Aysun; Kara, Murat; Karakecili, Faruk; Dabanlioglu, Bulent; Kemal Arslan, Yusuf (Annals of Medical Research, 2021)
Aim: We aimed to determine the genotype distribution in Hepatitis C patients who Parasitology applied to Erzincan Binali Yildirim University, Mengücek Gazi Training and Research Hospital. Hepatitis C virus, the only member of the genus Hepacivirus of Flaviviridae family, is responsible for 25%-40% of all liver diseases. Hepatitis C virus causes acute hepatitis C and chronic hepatitis C infections. Chronic hepatitis C infection causes cirrhosis, liver failure, hepatocellular cancerand liver diseases in terminal periods. Material and Methods: A total of 77 patients, 41 male and 36 female, who were admitted to Erzincan Binali Yıldırım University, Mengücek Gazi Training and Research Hospital in the period of January 2013-June 2019, were included in our study. RT-PCR and DNA sequencing for the 5’UTR region of the HCV genome for HCV genotyping was performed using the ABI Prism 3130 × 1 DNA Sequencer device.Results: Sex of a total of 77 patients included in the study; 41 of them are men (53.2%) and 36 are women (46.8%). Average age of the patients; It was 59.9 ± 16.6 (minimum 20 and maximum 94). HCV G1b (80.5%) in 62 patients, HCV G1a (7.8%) in 6, HCV G3a (3.9%) in 3, HCV G3 (2.6%) in 2 and HCV G2 (2.6%) was found in 2 patients. HCV G1 (1.3%) was detected in 1, HCV G4 (1.3%) in 1 patient.Conclusion: The dominant genotype in Hepatitis C patients who applied to Mengücek Gazi Training and Research Hospital was determined as “HCV Genotype 1b”.